Egg distribution, bottom topography and small-scale cod population structure in a coastal marine system - Knutsen, Halvor; Olsen, Esben Moland; Ciannelli, Lorenzo; Espeland, Sigurd Heiberg; Knutsen, Jan Atle; Simonsen, Jan Henrik; Skreslet, Stig; Stenseth, Nils Christian (Marine Ecology Progress Series, 2007)
Coastal marine species with pelagic egg and larval stages, such as the Atlantic cod Gadus morhua, can be structured into genetically distinct local populations on a surprisingly small geographic scale considering their dispersal potential. Mechanisms responsible for such small-scale genetic structure may involve homing of adults to their natal spawning grounds, but also local retention of pelagic eggs and larvae. For example, spawning within sheltered fjord habitats is expected to favour local retention of early life stages. Here, we studied the distribution of cod eggs along inshore– offshore transects in 20 Norwegian fjords. The general pattern exhibited across all fjords was a higher concentration of cod eggs inside the fjords than further offshore. In particular, fjords with shallow sills (model threshold 37 m) show an abrupt reduction in egg density over the sill. This study provides empirical support for an offspring retention hypothesis, which may help to explain the maintenance of local population structure in pelagic marine systems.